Native Endomycorrhiza With Tolerance to Heavy Metal Contamination in Organic Culture Media - Akib, Muh. Akhsan; Nuddin, Andi; Pradityaningsih, Retno; Antonius, Sarjiya; Kuswinanti, Tutik; Syaiful, Syatrianti Andi (KnE Life Sciences, 2022)
Endomycorrhizal fungi are spora-carrying organisms that can survive in heavy metalcontaminated environments. The goal of this study was to investigate endomycorrhizal fungi from heavy metal-affected areas and determine an effective mix of organic culture media to increase the number and diameter of endomycorrhizal spores. In Sorowako, Indonesia, endomycorrhizal fungi were isolated from the rhizosphere of: rice husk charcoal, sand, zeolite (KM1); rice husk charcoal, sand, sawdust (KM2); rice husk charcoal, sand, cocopeat (KM3); rice husk charcoal, sand, rice soil (KM4); rice husk charcoal, sand, cold magma (KM5); rice husk charcoal, sand, cold magma (KM6); and rice husk charcoal, sand (KM7). The results of the first phase of research revealed that three endomycorrhizal genera (44.44%–75.86% Acaulospora sp, 9.52%–44.44% Gigaspora sp, and 3.38%–19.05 % Glomus sp) can adapt to and resist conditions contaminated with Hg, Cd, Ni, Pb, As, Cr, Mn, Fe, Cu, Co, and Sn, namely as a carrier medium. It was concluded that a combination of organic media was recommended, but that this must decompose first. Keywords: Fungi, mycorrhizal, organic waste, rhizosfer